Strong terahertz absorption in all-dielectric Huygens' metasurfaces. (19th September 2016) - Cole, Michael A; Powell, David A; Shadrivov, Ilya V
Abstract: We propose an all dielectric metamaterial that acts as a perfect terahertz absorber without a ground plane. The unit cell consists of a dielectric cylinder embedded in a low index material. In order to achieve near-perfect terahertz absorption (99.5%) we employ impedance matching of the electric and magnetic resonances within the cylinders of the Huygens' metasurface. The impedance matching is controlled by changing the aspect ratio between the height and diameter of the cylinder. We show that the absorption resonance can be tuned to particular frequencies from 0.3 to 1.9 THz via changing the geometry of the structure while keeping a nearly constant aspect ratio of the cylinders.